Laboratory Quality Management Requirements of Engineering at the Polytechnics Ministry of Higher Education Malaysia - Zunuwanas Mohamad; Ruhizan Mohammad Yasin; Mohd Nizam Ab Rahman (Intelektual Pustaka Media Utama, 2012)
Engineering lab is instrumental in the technical fields of study. Continuity of learning theories in the classroom will be applied in the laboratory for understanding and exposure to engineering skills. This paper is a study that outlines the main aspects of quality management in the engineering laboratory (lab) to provide learning and teaching facilities in the labs. The roles and accountability of the lab management ensure appropriate management processes, preparation and execution of engineering laboratory work for students. A finding from the literature study raises important issues relating to laboratory quality management and should be addressed by the laboratory management personnel. Soundness of management of an engineering lab, depends on the relationship between management and network department, laboratory management, teaching staff and students. The key element of quality management is the management of engineering laboratory documentation, safety, environment and management tools.